2011
DOI: 10.1007/978-1-61779-325-7_18
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 Addition Increases Spot Size and Number as Measured by T-SPOT.TB ®

Abstract: The interferon-gamma (IFN-γ) release assay (IGRA) is an in vitro extension of the century-old in vivo tuberculin skin test, better known as the TST. Shortcomings to the TST are multifactorial and include limitations in sensitivity and specificity. IGRAs improve diagnostic specificity by using antigens not found in the Bacille Calmette-Guérin, a vaccine given in most countries. IGRAs capture the IFN-γ produced by T cells in response to antigen stimulation. The ELISPOT immediately captures IFN-γ produced directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Lipopolysaccharides (LPS) present in whole-cell lysates could also potentially stimulate the T cells, although Janský et al ( 18 ) showed that LPS from Escherichia coli did not result in elevated IFN-γ levels and that Borrelia lysates did. Other studies showed the production of IFN-γ by NK cells after stimulation with LPS ( 44 , 45 ); however, we tried to correct for this phenomenon by adjusting the ELISpot assay reader settings in which we omitted small- and low-intensity spots ( 35 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipopolysaccharides (LPS) present in whole-cell lysates could also potentially stimulate the T cells, although Janský et al ( 18 ) showed that LPS from Escherichia coli did not result in elevated IFN-γ levels and that Borrelia lysates did. Other studies showed the production of IFN-γ by NK cells after stimulation with LPS ( 44 , 45 ); however, we tried to correct for this phenomenon by adjusting the ELISpot assay reader settings in which we omitted small- and low-intensity spots ( 35 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of Borrelia -specific IFN-γ-producing T cells, displayed as black spots, was measured with an ELISpot reader (Autoimmun Diagnostika GmbH), visually checked, and, if judged necessary, adjusted manually by two different operators in the EliSpot 6.0 software (Autoimmun Diagnostika GmbH). The spot size used was based on the expected spot size of an IFN-γ-producing T cell as determined by Feske et al ( 35 ) and was set on −2.8 log (mm 2 ). If there was a difference in the T-cell count between the two operators of ≥4 spots for a certain sample, or if they found any difference in spot count in the critical area (between 2 and 5 spots), then those samples were recounted by a third operator, whose result was leading.…”
Section: Methodsmentioning
confidence: 99%
“…We have studied MCP-2 and found a lower sensitivity of 71% for active TB at 97% specificity in healthy controls, but no significant added effect by combination with either IP-10 or IFN-g [52]. In a subsequent eval uation in HIV-infected patients with confirmed TB, we observed significant lower sensitivity of MCP-2 compared with IFN-g and IP-10, and found no added effect by combination Tweaking of the incubation step, for example by increasing incubation temperature [49], prolonging the incubation period [23,92,93], improving culture conditions with nutrients [201] or addition of proinflammatory cytokines (e.g., IL-12 [85]), blocking of anti-inflammatory cytokines (e.g., IL-10 [49,94]) or adding 'survival' cytokines (e.g., IL-7 [95,96]), have also shown potential for augmentation of the antigen-specific immune response.…”
Section: Hot Topics and Unsolved Questionsmentioning
confidence: 99%
“…SFCs were counted without prior knowledge of the medical background of the study participants. The SFC size used was based on the expected SFC size of an IFN-γ-producing T cell, as determined by Feske et al [28], and was set on -2.8 log (mm 2 ). Samples that had a discrepancy in the numbers of SFCs between the two counting persons were recounted by a third person, whose result was leading.…”
Section: The In-house Borrelia Elispot Assaymentioning
confidence: 99%